Pengaruh Sistem Penilaian Kinerja Dan Reward Terhadap Kinerja Karyawan - Wiwin Rosmiyanti Agustin; Faizal Mulia Z; Dicky Jhoansyah (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to determine the effect of performance appraisal system variables and rewards on employee performance. This study uses quantitative methods. The population in this study are employees of PT. Paragon Technology And Innovation DC Sukabumi and the sample used was 100 respondents. The data analysis technique used is multiple linear regression analysis and the sample technique used is probability sampling. The results of this study indicate that simultaneously and partially the variables of the performance appraisal system and reward have a positive and significant effect on employee performance. The results of the f test are known from the Fcount 101.961 > 3.08 indicating that the Fcount value is greater than Ftable and the correlation results in this study have a strong and high value of 0.678. Meanwhile, from the results of the t-test value, namely Tcount 2,286 > 1,983, it shows that Tcount is greater than Ttable so it can be concluded that the performance appraisal and reward system variables have an influence on employee performance. Keywords: Performance Assessment, Reward, Employee Performance